First record of blackfin pearlfish Austrolebias nigripinnis (Regan, 1912 (Cyprinodontiformes, Cynolebiidae) from Brazil - Volcan, Matheus Vieira; Gonçalves, Ândrio Cardozo; Lanés, Luis Esteban Krause (Zootaxa, 2017)
Austrolebias Costa is a genus of annual fish inhabiting temporary wetlands in the Chaco-Pampasic region of southern Brazil, Uruguay, Paraguay, Bolivia and Argentina (Costa, 2006, Nielsen & Pillet, 2015, Alonso et al., 2016). Currently, about 45 species of Austrolebias are known (Costa, 2006, Volcan et al., 2014, Nielsen & Pillet, 2015), and of these, 24 occur in Rio Grande do Sul, the southernmost state of Brazil, distributed across the Rio Uruguay basin and the Patos-Mirim lagoon system and adjacent coastal areas (Volcan et al., 2015).